Rodziny zastępcze w Czechach w kontekście pedagogiki specjalnej - Starek, Lukas (Studia Edukacyjne, 2019)
The text focuses on the definition of substitute family care and its basic forms that are applied and used in the Czech Republic. The historical progression of substitute family care is also mentioned to demonstrate that this issue is a part of human society. An integral part of the text is the statistical information. Furthermore, the purpose of the text is to point out the need for experts and professionals who are engaged with this problem and are working with this targeted group. Last but not least is the need for reflection on those changes that had to be made because of the change in attitudes concerning substitute family care.